An analytical method for predicting the ship side structure response in raked bow collisions. (April 2015) - Sun, Bin; Hu, Zhiqiang; Wang, Ge
Abstract: As an increasing number of ships continue to sail in heavy traffic lanes, the possibility of collision between ships has become progressively higher. Therefore, it is of great importance to rapidly and accurately analyse the response and consequences of a ship's side structure subjected to large impact loads, such as collisions from supply vessels or merchant vessels. As the raked bow is a common design that has a high possibility of impacting a ship side structure, this study proposes an analytical method based on plastic mechanism equations for the rapid prediction of the response of a ship's side structure subjected to raked bow collisions. The new method includes deformation mechanisms of the side shell plating and the stiffeners attached. The deformation mechanisms of deck plating, longitudinal girders and transverse frames are also analysed. The resistance and energy dissipation of the side structure are obtained from individual components and then integrated to assess the complete crashworthiness of the side structure of the struck ship. The analytical prediction method is verified by numerical simulation. Three typical collision scenarios are defined in the numerical simulation using the code LS_DYNA, and the results obtained by the proposed analytical method and those of the numerical simulation are compared. The results correspond well, suggesting that the proposed analytical method can improve ship crashworthiness during the design phase. Highlights: An analytical prediction method for predicting responses of ship side structures is proposed. New simplified analytical models are developed for the side shell and attached stiffeners. The deformation mechanisms of web girders are analyzed. Several key steps for predicting the response of side structure are presented. The proposed method is verified by numerical simulation, the results match well.